2012
DOI: 10.1016/j.biomaterials.2011.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of bioactive molecules to the mitochondrial genome using a membrane-fusing, liposome-based carrier, DF-MITO-Porter

Abstract: Mitochondrial dysfunction has been implicated in a variety of human diseases. It is now well accepted that mutations and defects in the mitochondrial genome form the basis of these diseases. Therefore, mitochondrial gene therapy and diagnosis would be expected to have great medical benefits. To achieve such an innovative a strategy, it will be necessary to deliver therapeutic agents into mitochondria in living cells. We report here on a novel an approach to accomplish this via the use of a Dual Function (DF)-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 37 publications
0
38
0
3
Order By: Relevance
“…In a previous study, we reported on the development of a Dual Function (DF)-MITO-Porter, an innovative nanocarrier for achieving mitochondrial delivery, which has the ability to pass through the endosomal and mitochondrial membranes via step-wise membrane fusion (Yamada et al, 2011;Yamada et al, 2012a). In addition, we constructed the DF-MITO-Porter with oligodeoxynucleotide (oligo DNA) encapsulated, and estimated the intracellular multiple processes (Yamada et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported on the development of a Dual Function (DF)-MITO-Porter, an innovative nanocarrier for achieving mitochondrial delivery, which has the ability to pass through the endosomal and mitochondrial membranes via step-wise membrane fusion (Yamada et al, 2011;Yamada et al, 2012a). In addition, we constructed the DF-MITO-Porter with oligodeoxynucleotide (oligo DNA) encapsulated, and estimated the intracellular multiple processes (Yamada et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…A dual-function (DF) MITO-Porter version was recently described that possesses mitochondrionfusogenic inner and endosome-fusogenic outer envelopes and has the ability to pass through endosomal and mitochondrial membranes via stepwise membrane fusion (Yamada and Harashima 2012a). MITO-Porters reportedly delivered the nucleic acid stain propidium iodide (Yasuzaki et al 2010) and proteins such as green fluorescent protein (GFP; Yamada et al 2008) and DNase I (Yamada et al 2011; Yamada and Harashima 2012a) into the mitochondrial matrix.…”
Section: Mito-portersmentioning
confidence: 98%
“…The liposome's prepared with isolated mitochondrial fraction were also shown to deliver DNA to the mitochondria of mammalian cells [23]. Based on the ability of certain lipids to fuse with the mitochondrial membranes, another class of nanocarrier, MITO-Porters and more recently dual function MITO-Porters, having both endosome and mitochondria fusogenic envelope showed the delivery of GFP to human cells [24,25]. In all the above stated cases, though the system ensures intracellular delivery and subsequently promoted enhanced colocalization of the delivered DNA with mitochondria; whether the DNA actually got inside the organelle needs to be established.…”
Section: Dna Delivery To Mitochondriamentioning
confidence: 99%